Intersectoral linkages in oil palm industry between Malaysia and Indonesia - Abdul Hamid Jaafar; Norlida Hanim Mohd Salleh; Zulkifli Abdul Manaf (Penerbit Universiti Kebangsaan Malaysia, 2015)
Malaysia and Indonesia are both major producers of palm oil. The palm oil industry in both countries has contributed immensely to rural income and development. The purpose of this paper is to empirically contrast the similarities and differences in linkages between the Malaysian and Indonesian palm oil industry.The assessment is carried out using the hypothetical extraction method. Data used in this study were from Malaysian and Indonesian 2005 Input-Output Table. Empirical findings of this study revealed several similarities and differences of Malaysian and Indonesian palm oil industry. The linkage analyses in this paper indicated that for both Malaysia and Indonesia, the oil palm cultivation sector is economically more linked to the manufacturing sector than to the agriculture or service sectors. In other words, the cultivation sector not only has a strong economic pull on the manufacturing sector, but also strong economic push as well. The processing sector was found to be more backwardly linked to the agriculture sector and more forwardly linked to the manufacturing sector. Comparing the Malaysian palm oil industry to the Indonesian palm oil industry, the empirical findings indicated that the palm oil industry in Malaysia is more interconnected to the rest of the production sectors than it is in Indonesia. The overall implication of this is that the the Malaysian palm oil industry has greater influence on its economy than the industry does on the overall economy of Indonesia.